From Every People And Nation The Book of Revelation in Intercultural Perspective - Rhoads, David (Minneapolis Fortress Press, 2005)
"A diverse group of New Testament scholars and theologians offer myriad paths to a better understanding of the Book of Revelation. They discuss topics such as Hispanic/Cuban American and African American perspectives, ecological issues, postcolonial the
Keywords: New Testament - Revelation. Bible. -- Revelation -- Criticism, interpretation, etc. Bible. -- Revelation - Criticism, Interpretation, etc. Bible. -- New Testament. -- Apocalypse -- Critique, interprétation, etc. Bible. -- Revelation